Assessment of a New Global Ocean Reanalysis in ENSO Predictions With NOAA UFS - Jieshun Zhu; Wanqiu Wang; Arun Kumar; Yanyun Liu; David DeWitt (Geophysical Research Letters)
Abstract As an update on the current NOAA/NCEP operational ocean reanalysis systems, a new system named GLobal Ocean Reanalysis (GLORe) is recently built up based on the JEDI‐SOCA 3DVar scheme. In this study, the quality of GLORe is assessed in initializing ENSO predictions using the NOAA Unified Forecast System (UFS). In details, initialized by GLORe, 9‐month ensemble hindcasts are conducted from each May/November during 1982–2021. The ENSO prediction skill is compared to the current NOAA operational system CFSv2, suggesting that UFS initialized with GLORe has an improved skill in ENSO predictions. By conducting another set of hindcasts with UFS and the same initializations as CFSv2, it is found that the skill improvement is largely attributed to the ocean initialization with GLORe, but with some contributions from model improvements as well. The effect of ocean initializations is further confirmed by the superiority of GLORe over CFSR as validated against an objective analysis.